2012
DOI: 10.3348/kjr.2012.13.2.165
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Ultra-Low Dose CT in the Diagnosis of Pediatric-Like Fractures Using an Experimental Animal Study

Abstract: ObjectiveThe aim of this prospective study was to evaluate the performance of ultra-low dose CT for the diagnosis of pediatric-like fractures and ascertain the lowest dose level sufficient for diagnostics.Materials and MethodsFifty-one bones of young pig cadavers were artificially fractured and subsequently examined by using a 64 multi-detector CT with 36 various dose levels down to a dose comparable with that of X-rays. Two pediatric radiologists analysed the CT scans according to the presence or absence of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…Therefore, it is reasonable to assume that radiation dose reduction during CT examination is one of the most effective ways to reduce the total amount of radiation that a patient is exposed to. To compensate for the rapid increase in medical radiation exposure by CT, continued efforts have been made to reduce radiation dose and to develop radiation reduction techniques ( 3 , 6 - 10 ). Recently, two new radiation reduction techniques have been introduced.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is reasonable to assume that radiation dose reduction during CT examination is one of the most effective ways to reduce the total amount of radiation that a patient is exposed to. To compensate for the rapid increase in medical radiation exposure by CT, continued efforts have been made to reduce radiation dose and to develop radiation reduction techniques ( 3 , 6 - 10 ). Recently, two new radiation reduction techniques have been introduced.…”
Section: Introductionmentioning
confidence: 99%
“…This result is consistent with previous reports that dose-reduced CT was sufficient for diagnosis of fracture in cervical spine trauma [27] and in the experimental animal model. [28] However, subtle rib contour abnormality (buckle fracture) could not be easily detected using low-dose CT. Thus, additional coronal and sagittal reformatted images can be helpful for detection of fractures that are missed on axial images.…”
Section: Discussionmentioning
confidence: 99%
“…14 Wang et al 12 reported that when conducting an MDCT scan for orbital trauma, images acquired using 100 mA tube current (the conventional dose is 300 mA) met the clinical diagnostic requirements, resulting in decreased patient radiation exposure. With regard to extremity imaging, Moritz et al 15 demonstrated that ultra-low-dose CT (up to 11 mA) showed sufficient diagnostic performance for fractures, despite the significant radiation reduction. In this study, we used tube current half of standard dose CT and compared scan image quality and diagnostic performance between standard-dose and low-dose CT.…”
Section: Discussionmentioning
confidence: 99%